The rice LysM receptor‐like kinase OsCERK1 is required for the perception of short‐chain chitin oligomers in arbuscular mycorrhizal signaling. Issue 4 (29th March 2017) - Carotenuto, Gennaro; Chabaud, Mireille; Miyata, Kana; Capozzi, Martina; Takeda, Naoya; Kaku, Hanae; Shibuya, Naoto; Nakagawa, Tomomi; Barker, David G.; Genre, Andrea
Summary: The rice lysin‐motif (LysM) receptor‐like kinase Os CERK1 is now known to have a dual role in both pathogenic and symbiotic interactions. Following the recent discovery that the Oscerk1 mutant is unable to host arbuscular mycorrhizal (AM) fungi, we have examined whether Os CERK1 is directly involved in the perception of the short‐chain chitin oligomers (Myc‐COs) identified in AM fungal exudates and shown to activate nuclear calcium (Ca 2+ ) spiking in the rice root epidermis. An Oscerk1 knockout mutant expressing the cameleon NLS‐YC2.60 was used to monitor nuclear Ca 2+ signaling following root treatment with either crude fungal exudates or purified Myc‐COs. Compared with wild‐type rice, Ca 2+ spiking responses to AM fungal elicitation were absent in root atrichoblasts of the Oscerk1 mutant. By contrast, rice lines mutated in OsCEBiP, encoding the LysM receptor‐like protein which associates with Os CERK1 to perceive chitin elicitors of the host immune defense pathway, responded positively to Myc‐COs. These findings provide direct evidence that the bi‐functional Os CERK1 plays a central role in perceiving short‐chain Myc‐CO signals and activating the downstream conserved symbiotic signal transduction pathway.